2019
DOI: 10.31557/apjcp.2019.20.8.2303
|View full text |Cite
|
Sign up to set email alerts
|

Combined Hyperthermia and Radiation Therapy for Treatment of Hepatocellular Carcinoma

Abstract: Background:There is no doubt that hyperthermia is one of the powerful radiosensitizers. Finding a proper mechanism working in hyperthermia/radiation combination is still pronounced challenge.Objectives:This study is focusing on the anti-cancer activities (anti-proliferative, anti-angiogenic and antiapoptotic) of thermoradiotherapy. Materials and Methods:Liver cancer cell line (HepG2) was treated by 37oC, 40oC and 43oC hyperthermia degrees combined with three radiation doses (2 Gy, 4 Gy and 8 Gy) for 24, 48 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Direct absorption of ultrasound by tissues also induces hyperthermia and has been a major factor in anti-cancer therapies 34 . Hyperthermia, alone or in combination with other therapeutic modalities such as radiation therapy, chemical drugs, or ablative ultrasound therapy has been shown to enhance HCC treatment 14 , 16 , 35 . Likewise, hyperthermia induced by ultrasound has been demonstrated in efficient drug delivery in tumors 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct absorption of ultrasound by tissues also induces hyperthermia and has been a major factor in anti-cancer therapies 34 . Hyperthermia, alone or in combination with other therapeutic modalities such as radiation therapy, chemical drugs, or ablative ultrasound therapy has been shown to enhance HCC treatment 14 , 16 , 35 . Likewise, hyperthermia induced by ultrasound has been demonstrated in efficient drug delivery in tumors 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthermia has long been used as an adjunctive radio- and chemo-sensitizing therapeutic agent for HCC treatment 13 – 15 . Hyperthermia has shown to enhance radiation response in HCC by increasing radiation-induced cytotoxicity and inhibiting DNA damage repair mechanisms 16 . Under the normal course of hyperthermia, the presence of blood vessels in the targeted tissue region buffers the adjacent cells from the intended tissue damage by allowing thermal energy to dissipate via blood flow 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…When reaching con uence, monolayer cells were rinsed with phosphate buffered slaine (PBS) and harvested by trypsin/EDTA (Biowest) treatment. After treatment of cells with the formulations containg different concentration of HG and ST and incubation for 48 h at 37ºC, the plates were examined under the inverted microscope and proceeded for the MTT assay [25].…”
Section: Cell Viability Assaymentioning
confidence: 99%
“… 4 , 5 Thermotherapy could improve the hypoxia inside the tumor and boots the radiation therapeutic effects. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Thermotherapy could improve the hypoxia inside the tumor and boots the radiation therapeutic effects. 6,7 Heat shock has been suggested as a non-invasive and non-toxic alternative to induce gene expression locally using a heat-inducible promoter. 8,9 For example, Tang et al have demonstrated that a hetero gene with hsp70 promoter could be elevated to 10 to 500-fold over background by magnetic heat (43 °C).…”
Section: Introductionmentioning
confidence: 99%